Expression of circulating miR-200c and vascular endothelial growth factor-A (VEGF-A) mRNA as potential biomarker in human hepatocellular carcinoma - Nanda Qoriansas; Dede Renovaldi; Juwita Raditya; Puji Lestari; Nur Signa Gumilas; . Suharno; Didik Setyo Heriyanto; Neneng Ratnasari; Sofia Mubarika H (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Hepatocellular carcinoma (HCC) is a common liver disease that causes significant publichealth problems throughout the world, including in Indonesia. The HCC is the six mostcommon cancers and second cancer-related deaths among men in the world. Recentlyit was reported that the microRNA is an important player in hepatocarcinogenesis. Theexpression of MiRNA-200c is often regulated in primary HCC and HCC cell lines. Vascularendothelial growth factor-A (VEGF-A) is a regulator of angiogenesis that has been reportedas miR-200c target gene. This study was conducted to measure expression levels in miR-200c and mRNAVEGF-A and their potential role as biomarkers at HCC. A total of 36HCC patients and 36 healthy subjects were included in this study. The relative expressionof miRNA-200c and mRNA VEGF-A was quantified using reverse transcription real timequantitative PCR (qRT PCR). Relative expression was calculated using . Unpaired t-testwas used to compare the expression levels of circulating miRNA-200c and mRNA VEGF-Ain HCC patients and healthy subjects. Pearson test was used to determine correlationbetween circulating miR-200c expression and mRNA VEGF-A expression levels. Theexpression levels of circulating miR-200c in HCC patients were lower compared to healthysubjects although it was not significant (p = 0.258). Conversely, the expression levelsof circulating mRNA VEGF-A in HCC patients were significantly higher compared tohealthy subjects (p = 0.001). The relative expression levels of circulating miR-200c werenegatively correlated with mRNA VEGF-A in HCC patients. In conclusion, the expressionlevels of mRNA VEGF-A in HCC patients are significantly deregulated in compared tothat in healthy subjects. Negative correlation between circulating miRN-200c and mRNAVEGF-A expression levels are reported in HCC patients.